Hubble : a new window to the universe - Fischer, Daniel; Duerbeck, Hilmar W., 1948- (New York : Copernicus, 1996)
Describes the steps taken to deploy the Hubble Space Telescope, and uses text and illustrations to describe the information gained so far, including the discovery of the second known supermassive black hole, and the first direct observation of a "core collapse" in a globular cluster.
Translated from the German.
Includes bibliographical references (p. 170-171) and index.
Adult
Keywords: Hubble Space Telescope (Spacecraft); Hubble Space Telescope (Spacecraft) -- History; Hubble Space Telescope (Spacecraft); Hubble Space Telescope (Spacecraft) -- History; Astronomy -- Pictorial works; Space astronomy; Astronomy; Universe -- Pictorial works